THE IMPACT OF THE CUSTOMS UNION AND THE EAEU ON THE SMALL AND MEDIUM BUSINESS IN KAZAKHSTAN - SHKVARYA, Lyudmila; KARABULATOVA, Irina; RUSAKOVICH, Vasily; RAPIEV, Abdulla (CENTRAL ASIA AND THE CAUCASUS, 2017)
The Customs Union (CU) and the Eurasian Economic Union (EAEU) serve as key mechanisms for protecting domestic markets within their member states by promoting coordinated foreign trade policies. These unions aim to foster the development of non-primary sectors, with a particular focus on modernizing, diversifying, and boosting the competitiveness of their economies. For the EAEU member countries—Russia, Belarus, Kazakhstan, Kyrgyzstan, and Armenia—developing small and medium-sized enterprises (SMEs) is increasingly important, especially in the face of economic challenges such as the recession and Western sanctions imposed on Russia, the largest economy in the EAEU. Despite this, SMEs in these countries encounter several obstacles. This article provides an analysis of the current state and developmental trends of small and medium businesses in Kazakhstan, particularly since the formation of the Customs Union in 2010 and the EAEU on January 1, 2015. It highlights various forms of government support available to SMEs and argues for the creation of a unified strategy to regulate small and medium business activities across the EAEU. The authors identify challenges in Kazakhstan’s economy as it integrates with the Customs Union and EAEU, emphasizing issues stemming from insufficient interaction between businesses and government entities.